Cubic and hexagonal liquid crystals as drug carriers for the transdermal delivery of triptolide - Qian-Qian Shan; Xiao-Jing Jiang; Fang-Yuan Wang; Zi-Xuan Shu; Shuang-Ying Gui (Taylor & Francis Group, 2019)
The purpose of this study was to develop and evaluate triptolide-loaded cubic and hexagonal liquid crystals for transdermal drug delivery systems (TDDSs). We prepared and characterized triptolide-loaded lyotropic liquid crystals and evaluated for their percutaneous permeation properties in vitro and in vivo. We then used the adjuvant arthritic rat model and HaCaT cells to analyze the pharmacodynamics and conduct cell-stimulating studies of these liquid crystals. The optimized preparations were identified as cubic and hexagonal phase structures, respectively. Moreover, the in vitro percutaneous penetration studies demonstrated that compared to the homemade triptolide gel, cubic and hexagonal liquid crystals could significantly increase the percutaneous cumulative penetration of drugs within 48 h. Besides, the results of skin-blood synchronous microdialysis showed that the triptolide concentration in skin was higher than that in blood, and the cubic and hexagonal liquid crystals significantly increased the bioavailability of triptolide. Triptolide-loaded cubic and hexagonal liquid crystals presented excellent anti-arthritic effects, alleviating paw swelling and inhibiting inflammation by downregulating the levels of TNF-α and IL-1β. In vitro cell-stimulating studies displayed that triptolide-loaded cubic and hexagonal liquid crystals exhibited no obvious toxicity, which exhibited that triptolide-loaded cubic and hexagonal liquid crystals were remarkable biocompatibility. Collectively, triptolide-loaded cubic and hexagonal liquid crystals represented a promising candidate for rheumatoid arthritis therapy.